Membrane electrode assembly for fuel cells and polymer electrolyte fuel cells

The membrane electrode assembly with oxide-based catalysts made from transition metals like Ta, Nb, or Ti, addresses the inefficiency of platinum catalysts by enhancing power generation and gas diffusivity in polymer electrolyte fuel cells, particularly in humidified conditions.

JP7615561B2Active Publication Date: 2025-01-17TOPPAN HOLDINGS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020135001
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-08
Filing Date
2020-08-07
Publication Date
2025-01-17
Estimated Expiration
2040-08-07

AI Technical Summary

Technical Problem

Current polymer electrolyte fuel cells rely on expensive platinum catalysts, particularly in the air electrode, and existing non-platinum alternatives exhibit insufficient oxygen reduction ability and stability in acidic electrolytes.

Method used

A membrane electrode assembly with electrode catalyst layers containing a noble metal component, a polymer electrolyte, and a fibrous material with an oxide catalyst made from transition metals like Ta, Nb, or Ti, which are partially oxidized nitrides, enhances the catalyst's durability and gas diffusivity.

Benefits of technology

The catalyst layer improves power generation characteristics by effectively discharging water and increasing reaction gas diffusivity, maintaining high performance under humidified conditions without deteriorating mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615561000001
    Figure 0007615561000001
  • Figure 0007615561000002
    Figure 0007615561000002
Patent Text Reader

Abstract

To provide a membrane-electrode assembly for a fuel battery, which has an electrode catalyst layer showing a high power generation characteristic.SOLUTION: A membrane-electrode assembly for a fuel battery comprises: a polymer electrolyte membrane 1; and a pair of electrode catalyst layers 2, 3 holding the polymer electrolyte membrane 1 therebetween. At least one of the pair of electrode catalyst layers 2, 3 includes: a particle which supports a catalyst comprising a noble metal component; a polyelectrolyte; a fibrous material having an average fiber length within a range of 1 μm up to 15 μm; and an oxide catalyst material. The oxide catalyst material includes at least one transition metal element selected from a group consisting of Ta, Nb, Ti and Zr.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a membrane electrode assembly for a fuel cell and a polymer electrolyte fuel cell. [Background technology]

[0002] A fuel cell is a power generation system that uses a fuel gas containing hydrogen and an oxidant gas containing oxygen to generate electricity and heat by inducing a reverse reaction of the electrolysis of water at electrodes containing a catalyst. This power generation system is highly efficient, has a low environmental impact, and is quieter than conventional power generation methods, and is attracting attention as a clean energy source for the future. There are several types of fuel cells depending on the type of ion conductor used, and fuel cells that use a proton-conducting polymer membrane are called solid polymer fuel cells.

[0003] Among fuel cells, solid polymer fuel cells can be used at around room temperature, and are therefore seen as promising for use as vehicle-mounted power sources and stationary home power sources, and in recent years, various research and development efforts have been conducted on them. Solid polymer fuel cells are cells in which a membrane electrode assembly (hereinafter sometimes referred to as MEA), in which electrode catalyst layers are arranged on each side of a polymer electrolyte membrane, is sandwiched between a pair of separators.

[0004] One of the separators has a gas flow path formed therein for supplying a fuel gas containing hydrogen to one of the electrodes, and the other separator has a gas flow path formed therein for supplying an oxidizer gas containing oxygen to the other of the electrodes.

[0005] Here, the one electrode to which the fuel gas is supplied is referred to as the fuel electrode, and the other electrode to which the oxidant gas is supplied is referred to as the air electrode. These electrodes are provided with an electrode catalyst layer having a polymer electrolyte, carbon particles (catalyst-supported particles) supporting a catalyst such as a platinum-based precious metal, and a gas diffusion layer having both gas permeability and electronic conductivity. The gas diffusion layer constituting these electrodes is disposed so as to face the separator, i.e., between the electrode catalyst layer and the separator.

[0006] Efforts have been made to improve the gas diffusion of the electrode catalyst layer in order to increase the power density of fuel cells. One of these efforts concerns the pores in the electrode catalyst layer. The pores in the electrode catalyst layer are located beyond the separator through the gas diffusion layer, and act as passages to transport multiple substances. At the fuel electrode, the pores not only smoothly supply fuel gas to the three-phase interface, which is the site of the redox reaction, but also supply water to smoothly conduct the generated protons within the polymer electrolyte membrane. At the air electrode, the pores not only supply oxidant gas, but also smoothly remove water generated in the electrode reaction.

[0007] Expensive platinum is used as an electrode catalyst in current polymer electrolyte fuel cells, and there is a strong demand for the development of alternative materials in order for them to become widespread. In particular, since more platinum is used in the air electrode than in the fuel electrode, there has been active development of platinum alternative materials (non-platinum catalysts) that exhibit high oxygen reduction catalytic activity in the air electrode.

[0008] As an example of a non-platinum catalyst in an air electrode, for example, Patent Document 1 describes a mixture of a nitride of iron, which is a transition metal, and a precious metal. Also, Patent Document 2 describes a nitride of molybdenum, which is a transition metal. However, the catalytic substances described in Patent Documents 1 and 2 have insufficient oxygen reduction ability in an acidic electrolyte, and the catalytic substances may dissolve. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2005-44659 A [Patent Document 2] JP 2005-63677 A Summary of the Invention [Problem to be solved by the invention]

[0010] An object of the present invention is to provide a membrane electrode assembly for a fuel cell, which has an electrode catalyst layer that exhibits high power generation characteristics when used in a polymer electrolyte fuel cell. [Means for solving the problem]

[0011] A membrane electrode assembly for a fuel cell for solving the above problems includes a polymer electrolyte membrane and a pair of electrode catalyst layers sandwiching the polymer electrolyte membrane. At least one of the pair of electrode catalyst layers includes particles carrying a catalyst made of a precious metal component, a polymer electrolyte, a fibrous material having an average fiber length in the range of 1 μm to 15 μm, and an oxide-based catalyst material. The oxide-based catalyst material includes at least one transition metal element selected from the group consisting of Ta, Nb, Ti, and Zr. Effect of the Invention

[0012] According to the present invention, it is possible to provide an electrode catalyst layer that exhibits high power generation characteristics when used in a polymer electrolyte fuel cell. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is an exploded perspective view showing a schematic structure of a membrane electrode assembly having a fuel cell electrode catalyst layer according to one embodiment of the present invention; [Diagram 2] FIG. 2 is an exploded perspective view showing a schematic structure of a polymer electrolyte fuel cell including the membrane electrode assembly of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. Here, the drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each layer, etc. are different from the actual ones. In addition, the embodiments shown below are examples of configurations for embodying the technical idea of ​​the present disclosure, and the technical idea of ​​the present disclosure is not limited to the materials, shapes, structures, etc. of the components described below. The technical idea of ​​the present disclosure can be modified in various ways within the technical scope defined by the claims described in the claims.

[0015] [Membrane electrode assembly] As shown in FIG. 1, a membrane electrode assembly 11 of this embodiment includes a polymer electrolyte membrane 1 and a pair of electrode catalyst layers 2, 3 that sandwich the polymer electrolyte membrane 1 from above and below.

[0016] Each of the electrode catalyst layers 2, 3 includes particles carrying a catalyst made of at least a precious metal component and a polymer electrolyte. At least one of the pair of electrode catalyst layers 2, 3 (hereinafter also referred to as the first electrode catalyst layer) includes an oxide-based catalyst material and a fibrous material.

[0017] The oxide-based catalytic material contained in the first electrode catalyst layer contains at least one transition metal element selected from the group consisting of Ta, Nb, Ti, and Zr. The oxide-based catalytic material is preferably a material obtained by partially oxidizing a nitride having P introduced as a substituting atom, and more preferably the transition metal element is Ti. In other words, the oxide-based catalytic material is made of a material obtained by partially oxidizing a nitride of a transition metal element containing P as a substituting atom.

[0018] In the first electrode catalyst layer, the ratio (MB / MA) of the mass (MB) of the oxide-based catalyst material to the mass (MA) of the support in the catalyst-loaded particle is preferably within the range of 0.1 to 10 times, and more preferably within the range of 0.8 to 4 times.

[0019] In the first electrode catalyst layer, the ratio (MC / MA) of the mass (MC) of the polymer electrolyte to the mass (MA) of the carrier in the catalyst-supported particles is preferably within the range of 0.2 to 2.8 times, and more preferably within the range of 0.6 to 1.2 times.

[0020] In the first electrode catalyst layer, the ratio (MD / MA) of the mass (MD) of the fibrous material to the mass (MA) of the support in the catalyst-loaded particle is preferably within the range of 0.05 to 1.0, and more preferably within the range of 0.1 to 0.4.

[0021] The particles carrying a catalyst made of a precious metal component contained in the first electrode catalyst layer are preferably covered with a hydrophobic coating.

[0022] The inventors of the present application have confirmed that the first electrode catalyst layer having the following configuration has drainage properties. The detailed mechanism by which the first electrode catalyst layer has drainage properties is presumed to be as follows. The present invention is not limited to the mechanism described below.

[0023] In the first electrode catalyst layer, the fibrous material is entangled, which makes it possible to suppress the occurrence of cracks in the electrode catalyst layer that reduce the durability of the first electrode catalyst layer. This results in a first electrode catalyst layer with high durability and mechanical properties. In addition, pores are formed in the electrode catalyst layer due to the entanglement of the particles carrying a catalyst made of a precious metal component, the oxide-based catalyst material, and the fibrous material. When a polymer electrolyte fuel cell including the first electrode catalyst layer is driven in a high current range, it is presumed that the pores can discharge water generated in the electrode reaction, and the diffusibility of the reaction gas can be improved. On the other hand, when the first electrode catalyst layer does not contain a fibrous material, entanglement does not occur between the particles carrying a catalyst made of a precious metal component and the oxide-based catalyst material, so that pores are unlikely to be formed in the electrode catalyst layer. Therefore, it is difficult to discharge the water generated in the electrode reaction, and as a result, it is presumed that when a polymer electrolyte fuel cell including the electrode catalyst layer is driven in a high current range, the diffusibility of the reaction gas cannot be improved.

[0024] It is estimated that if the average fiber length of the fibrous material is less than 1 μm, the mechanical properties of the electrode catalyst layer may be reduced. Also, if the average fiber length exceeds 15 μm, it is estimated that the ink may not be able to disperse. That is, by making the average fiber length of the fibrous material 1 μm or more, the deterioration of the mechanical properties of the electrode catalyst layer is suppressed. Also, by making the average fiber length of the fibrous material 15 μm or less, the fibrous material is easily dispersed in the ink for forming the electrode catalyst layer.

[0025] It is estimated that when the mass of the oxide-based catalytic material is less than 0.1 times the mass of the carrier in the catalyst-supported particle, it may be difficult to draw a sufficient current due to the low catalytic activity of the oxide-based catalytic material. In other words, by making the ratio of the mass of the oxide-based catalytic material to the mass of the carrier in the catalyst-supported particle 0.1 or more, the catalytic activity of the oxide-based catalytic material is prevented from decreasing, and thus it is possible to generate a sufficient current.

[0026] Moreover, if it exceeds 10 times, it is presumed that the thickened electrode catalyst layer may cause a decrease in current. In other words, by keeping the ratio of the mass of the oxide catalyst material to the mass of the carrier in the catalyst-supported particles at 10 times or less, the electrode catalyst layer is prevented from becoming excessively thick, and this makes it possible to suppress a decrease in current.

[0027] It is presumed that if the mass of the polymer electrolyte is less than 0.2 times the mass of the carrier in the catalyst-supported particles, it may be difficult to draw a sufficient current due to the influence of a decrease in the proton conductivity of the electrode catalyst layer. In other words, by making the mass of the polymer electrolyte 0.2 times or more the mass of the carrier in the catalyst-supported particles, the decrease in the proton conductivity of the electrode catalyst layer is suppressed, and thus it is possible to generate a sufficient current.

[0028] Moreover, if it exceeds 2.8 times, it is estimated that the diffusibility of the reactant gas may not be improved due to the influence of the reduction in the pores formed in the electrode catalyst layer. In other words, by making the mass of the polymer electrolyte 2.8 times or less relative to the mass of the carrier in the catalyst-supported particles, the reduction in the pores in the electrode catalyst layer is suppressed, and thus the diffusibility of the reactant gas can be improved.

[0029] It is estimated that when the mass of the fibrous material is less than 0.05 times the mass of the carrier in the catalyst-supported particle, the mechanical properties of the electrode catalyst layer may be reduced. That is, when the ratio of the mass of the fibrous material to the mass of the carrier in the catalyst-supported particle is 0.05 times or more, the reduction in the mechanical properties of the electrode catalyst layer is suppressed. Also, when it exceeds 1.0 times, it is estimated that the current may be reduced due to the influence of the thickened electrode catalyst layer. That is, when the ratio of the mass of the fibrous material to the mass of the carrier in the catalyst-supported particle is 1.0 times or less, the electrode catalyst layer is prevented from becoming excessively thick, and thus the reduction in the current can be suppressed.

[0030] Unlike conventional methods of improving drainage by changing the configuration of the electrode catalyst layer, the membrane electrode assembly 11 of this embodiment does not exhibit a decrease in power generation characteristics due to an increase in interface resistance. As a result, a polymer electrolyte fuel cell including the membrane electrode assembly 11 has higher power generation characteristics in the high current region where a large amount of water is generated, compared to a polymer electrolyte fuel cell including a conventional membrane electrode assembly.

[0031] [Polymer electrolyte fuel cell] Next, a polymer electrolyte fuel cell including a membrane electrode assembly 11 according to the embodiment will be described with reference to FIG.

[0032] The polymer electrolyte fuel cell 12 shown in Fig. 2 includes a pair of gas diffusion layers 4, 5. The gas diffusion layer 4 is disposed so as to face the electrode catalyst layer 2 of the membrane electrode assembly 11. The gas diffusion layer 5 is disposed so as to face the electrode catalyst layer 3. The electrode catalyst layer 2 and the gas diffusion layer 4 form an air electrode (cathode, positive electrode) 6. The electrode catalyst layer 3 and the gas diffusion layer 5 form a fuel electrode (anode, negative electrode) 7.

[0033] A pair of separators 10a, 10b are disposed on the outer sides of the gas diffusion layers 4, 5, respectively. That is, the membrane electrode assembly 11 is sandwiched between the pair of separators 10a, 10b in the thickness direction of the membrane electrode assembly 11. The separators 10a, 10b include gas flow paths 8a, 8b for gas flow and cooling water flow paths 9a, 9b for cooling water flow. The separators 10a, 10b are formed of a material having electrical conductivity and impermeability.

[0034] A fuel gas, for example, hydrogen gas, is supplied to the gas flow passage 8b of the separator 10b facing the fuel electrode 7. On the other hand, an oxidizer gas, for example, oxygen gas, is supplied to the gas flow passage 8a of the separator 10a facing the air electrode 6. An electromotive force can be generated between the fuel electrode 7 and the air electrode 6 by causing an electrode reaction between the hydrogen fuel gas and the oxygen oxidizer gas in the presence of a catalyst.

[0035] In the solid polymer fuel cell 12, a pair of separators 10a, 10b sandwich a polymer electrolyte membrane 1, a pair of electrode catalyst layers 2, 3, and a pair of gas diffusion layers 4, 5. The solid polymer fuel cell 12 shown in Fig. 2 is an example of a fuel cell having a single cell structure, but the solid polymer fuel cell may have a structure in which a plurality of cells are stacked with the separator 10a or the separator 10b interposed therebetween.

[0036] [Method for producing electrode catalyst layer] Next, an example of a method for producing the first electrode catalyst layer will be described. The first electrode catalyst layer is manufactured by a method including the following first and second steps. The first step is a step of manufacturing a catalyst ink containing catalyst-supporting particles, an oxide-based catalyst material, a fibrous material, a polymer electrolyte, and a solvent. The second step is a step of forming the first electrode catalyst layer by applying the catalyst ink obtained by the first step onto a substrate and drying the solvent. The second electrode catalyst layer, which is not the first electrode catalyst layer, may also be manufactured by the same steps. However, the second electrode catalyst layer does not contain the oxide-based catalyst material contained in the first electrode catalyst layer. Then, the pair of electrode catalyst layers 2 and 3 thus manufactured are attached to the opposing surfaces of the polymer electrolyte membrane 1 to obtain a membrane electrode assembly 11.

[0037] 〔detail〕 The membrane electrode assembly 11 and the polymer electrolyte fuel cell 12 will be described in more detail below. The polymer electrolyte membrane 1 may be any membrane having proton conductivity, such as a fluorine-based polymer electrolyte membrane or a hydrocarbon-based polymer electrolyte membrane. Examples of the fluorine-based polymer electrolyte membrane that can be used include Nafion (registered trademark) manufactured by DuPont, Flemion (registered trademark) manufactured by Asahi Glass Co., Ltd., Aciplex (registered trademark) manufactured by Asahi Kasei Corporation, and Gore Select (registered trademark) manufactured by Gore.

[0038] Examples of the hydrocarbon-based polymer electrolyte membrane include sulfonated polyether ketone, It is possible to use an electrolyte membrane made of sulfonated polyethersulfone, sulfonated polyetherethersulfone, sulfonated polysulfide, sulfonated polyphenylene, etc. In particular, it is preferable to use a Nafion (registered trademark) material manufactured by DuPont as the polymer electrolyte membrane 1.

[0039] The electrode catalyst layers 2, 3 are formed on both sides of the polymer electrolyte membrane 1 using a catalyst ink. The catalyst ink for the electrode catalyst layers 2, 3 contains catalyst-supporting particles, a polymer electrolyte, and a solvent. The catalyst ink for the improved electrode catalyst layer contains catalyst-supporting particles, an oxide-based catalyst material, a polymer electrolyte, and a solvent.

[0040] The polymer electrolyte contained in the catalyst ink may be any material having proton conductivity. The polymer electrolyte may be made of the same material as that of the polymer electrolyte membrane 1. The polymer electrolyte may be made of, for example, a fluorine-based polymer electrolyte or a hydrocarbon-based polymer electrolyte. The fluorine-based polymer electrolyte may be made of, for example, a Nafion (registered trademark)-based material manufactured by DuPont. The hydrocarbon-based polymer electrolyte may be made of, for example, a sulfonated polyether ketone, a sulfonated polyether sulfone, a sulfonated polyether ether sulfone, a sulfonated polysulfide, or a sulfonated polyphenylene. In particular, it is preferable to use a Nafion (registered trademark)-based material manufactured by DuPont as the fluorine-based polymer electrolyte.

[0041] The catalyst made of a precious metal component used in this embodiment may be, for example, a metal or alloy, a metal oxide, or a metal composite oxide. Examples of the metal include one or more metals selected from the group consisting of platinum, palladium, ruthenium, iridium, and rhodium. The composite oxide referred to here is an oxide made of two types of metals.

[0042] The average particle diameter of the above-mentioned catalyst is preferably within the range of 0.5 nm to 20 nm, more preferably within the range of 1 nm to 5 nm. Here, the average particle diameter is the average particle diameter obtained by X-ray diffraction in the case of particles carrying a catalyst including a carrier such as carbon particles and a catalyst supported on the carrier. In the case of a catalyst not supported on a carrier, it is the arithmetic average particle diameter obtained by particle size measurement. When the average particle diameter of the catalyst particles is within the range of 0.5 nm to 20 nm, the activity and stability of the catalyst are improved, which is preferable.

[0043] Carbon particles are generally used as the electron conductive powder that supports the above-mentioned catalyst, i.e., the carrier. The type of carbon particles is not limited as long as they are fine particles, conductive, and not affected by the catalyst. Examples of carbon particles that can be used include carbon black, graphite, activated carbon, carbon fiber, carbon nanotubes, and fullerenes.

[0044] The average particle diameter of the carbon particles is preferably within the range of 10 nm to 1000 nm, more preferably within the range of 10 nm to 100 nm. Here, the average particle diameter is the average particle diameter obtained from an SEM image. When the average particle diameter of the carbon particles is within the range of 10 nm to 1000 nm, the activity and stability of the catalyst are improved, which is preferable. In addition, when the average particle diameter of the carbon particles is within the range of 10 nm to 1000 nm, an electron conduction path is easily formed, and the gas diffusion properties and catalyst utilization rate of the two electrode catalyst layers 2 and 3 are improved, which is preferable.

[0045] The above-mentioned catalyst-supporting particles may be provided with a hydrophobic coating. In other words, the particles supporting the catalyst may be covered with a hydrophobic coating. In this case, it is preferable that the hydrophobic coating has a thickness that allows the reaction gas to pass through sufficiently. Specifically, the thickness of the hydrophobic coating is preferably 40 nm or less. If the thickness is greater than this, the supply of the reaction gas to the active points may be hindered. On the other hand, if the hydrophobic coating is 40 nm or less, the reaction gas can pass through the hydrophobic coating sufficiently, and therefore the catalyst-supporting particles can be provided with hydrophobicity.

[0046] In addition, the thickness of the hydrophobic coating covering the catalyst-supporting particles is preferably a thickness that sufficiently repels the generated water. Specifically, the thickness of the hydrophobic coating is preferably 2 nm or more. If the hydrophobic coating is thinner than this, the generated water may accumulate, and the supply of the reaction gas to the active points may be hindered. That is, by having the hydrophobic coating have a thickness of 2 nm or more, the accumulation of the generated water is suppressed, and thus the supply of the reaction gas to the active points is prevented from being hindered.

[0047] The hydrophobic coating covering the catalyst-supporting particles is formed, for example, from a fluorine-based compound having at least one polar group. Examples of the polar group include a hydroxyl group, an alkoxy group, a carboxyl group, an ester group, an ether group, a carbonate group, and an amide group. The presence of the polar group allows the fluorine-based compound to be fixed to the outermost surface of the electrode catalyst layer. The portion other than the polar group in the fluorine-based compound is preferably a structure consisting of fluorine and carbon because of its high hydrophobicity and chemical stability. However, the hydrophobic coating is not limited to such a structure as long as it has sufficient hydrophobicity and chemical stability.

[0048] In the present disclosure, the oxide-based catalytic material may be a material containing at least one selected from the group consisting of Ta, Nb, Ti, and Zr. The oxide-based catalytic material is preferably used as a substitute for platinum in the electrode catalyst layer of the air electrode, i.e., the positive electrode.

[0049] More preferably, a material obtained by introducing P as a substitution atom into the nitride of these transition metal elements and partially oxidizing the nitride in an atmosphere containing oxygen can be used. That is, the oxide-based catalyst material is a material in which a part of a fiber metal nitride containing phosphorus (P) is oxidized. In other words, the oxide-based material contains a transition metal atom, a nitrogen atom, a phosphorus atom, and an oxygen atom. That is, in the transition metal nitride, a part of the transition metal atom is substituted with a phosphorus atom.

[0050] Specifically, TiONP is a material that is produced by partially oxidizing Ti nitride (TiNP) with P introduced as a substitution atom in an atmosphere containing oxygen. In this case, some of the titanium atoms in titanium nitride (TiN) are replaced with phosphorus atoms. Also, some of the titanium nitride is oxidized.

[0051] As the fibrous material, for example, an electron conductive fiber and a proton conductive fiber can be used. Examples of the electron conductive fiber include carbon fiber, carbon nanotube, carbon nanohorn, and conductive polymer nanofiber. From the viewpoint of electrical conductivity and dispersibility, it is preferable to use a carbon nanofiber as the fibrous material.

[0052] The proton conductive fiber may be a fiber obtained by processing a polymer electrolyte having proton conductivity into a fiber shape. That is, the proton conductive fiber is a fiber formed by a polymer electrolyte having proton conductivity. The material for forming the proton conductive fiber may be a fluorine-based polymer electrolyte, a hydrocarbon-based polymer electrolyte, or the like. The fluorine-based polymer electrolyte may be, for example, Nafion (registered trademark) manufactured by DuPont, Flemion (registered trademark) manufactured by Asahi Glass Co., Ltd., Aciplex (registered trademark) manufactured by Asahi Kasei Corporation, and Gore Select (registered trademark) manufactured by Gore. The hydrocarbon-based polymer electrolyte may be an electrolyte such as sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polyether ether sulfone, sulfonated polysulfide, and sulfonated polyphenylene. Among these, it is preferable to use Nafion (registered trademark) manufactured by DuPont as the polymer electrolyte.

[0053] The fibrous material may be one of the above-mentioned fibers, or two or more of them. The fibrous material may be a combination of an electron conductive fiber and a proton conductive fiber. Among the above-mentioned fibrous materials, the fibrous material preferably includes at least one selected from the group consisting of carbon nanofibers, carbon nanotubes, and electrolyte fibers.

[0054] The solvent used as the dispersion medium of the catalyst ink is not particularly limited as long as it does not corrode the catalyst-supported particles, the oxide-based catalyst material, the fibrous material, and the polymer electrolyte, and can dissolve the polymer electrolyte in a highly fluid state or disperse it as a fine gel. However, it is preferable that the solvent contains at least a volatile organic solvent. The solvent used as the dispersion medium of the catalyst ink may be an alcohol, a ketone-based solvent, an ether-based solvent, a polar solvent, etc. The alcohol may be methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, pentanol, etc. The ketone-based solvent may be acetone, methyl ethyl ketone, pentanone, methyl isobutyl ketone, heptanone, cyclohexanone, methyl cyclohexanone, acetonyl acetone, diisobutyl ketone, etc. The ether-based solvent may be tetrahydrofuran, dioxane, diethylene glycol dimethyl ether, anisole, methoxytoluene, dibutyl ether, etc. The polar solvent may be dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, diethylene glycol, diacetone alcohol, 1-methoxy-2-propanol, etc. The solvent may also be a mixed solvent in which two or more of the above-mentioned materials are mixed.

[0055] In addition, since a dispersion medium using a lower alcohol has a high risk of ignition, it is preferable to use a mixed solvent of a lower alcohol and water when using a lower alcohol as the dispersion medium. Furthermore, the dispersion medium may contain water that is compatible with the polymer electrolyte, i.e., water that has a high affinity for the polymer electrolyte. The amount of water added to the dispersion medium is not particularly limited as long as the polymer electrolyte does not separate and become cloudy or gel.

[0056] In order to disperse the catalyst-supporting particles in the catalyst ink, the catalyst ink may contain a dispersant, such as an anionic surfactant, a cationic surfactant, an amphoteric surfactant, or a nonionic surfactant.

[0057] Examples of anionic surfactants include alkyl ether carboxylates, ether carboxylates, alkanoyl sarcosines, alkanoyl glutamates, acyl glutamates, oleic acid·N-methyl taurine, potassium oleate·diethanolamine salts, alkyl ether sulfate·triethanolamine salts, polyoxyethylene alkyl ether sulfate·triethanolamine salts, amine salts of specially modified polyether ester acids, amine salts of higher fatty acid derivatives, amine salts of specially modified polyester acids, amine salts of high molecular weight polyether ester acids, amine salts of specially modified phosphate esters, amidoamine salts of high molecular weight polyester acids, amidoamine salts of special fatty acid derivatives, alkylamine salts of higher fatty acids, amidoamine salts of high molecular weight polycarboxylic acids, carboxylic acid surfactants such as sodium laurate, sodium stearate, and sodium oleate, dialkyl sulfosuccinates, dialkyl sulfosuccinates, 1,Sulfonic acid surfactants such as 2-bis(alkoxycarbonyl)-1-ethanesulfonate, alkylsulfonate, paraffin sulfonate, α-olefin sulfonate, linear alkylbenzenesulfonate, alkylbenzenesulfonate, polynaphthylmethanesulfonate, naphthalenesulfonate-formaldehyde condensate, alkylnaphthalenesulfonate, alkanoylmethyltauride, sodium lauryl sulfate, sodium cetyl sulfate, sodium stearyl sulfate, sodium oleyl sulfate, lauryl ether sulfate, sodium alkylbenzenesulfonate, oil-soluble alkylbenzenesulfonate, and α-olefinsulfonate, alkyl sulfate, alkyl sulfate, alkyl ether sulfate, and polyoxyethylene alkyl ether sulfate. phosphate, alkyl polyethoxy sulfate, polyglycol ether sulfate, alkyl polyoxyethylene sulfate, sulfated oil, highly sulfated oil, and other sulfate ester surfactants; (mono- or di-) alkyl phosphate, (mono- or di-) alkyl phosphate, (mono- or di-) alkyl phosphate ester salt, alkyl polyoxyethylene phosphate, alkyl ether phosphate, alkyl polyethoxy phosphate, polyoxyethylene alkyl ether, alkyl phenyl polyoxyethylene phosphate, alkyl phenyl ether phosphate, alkyl phenyl polyethoxy phosphate, polyoxyethylene alkyl phenyl ether phosphate, higher alcohol phosphate monoester disodium salt, higher alcohol phosphate diester disodium salt, and zinc dialkyl dithiophosphate, and other phosphate ester surfactants.

[0058] Examples of cationic surfactants include benzyldimethyl{2-[2-(P-1,1,3,3-tetramethylbutylphenoxy)ethoxy]ethyl}ammonium chloride, octadecylamine acetate, tetradecylamine acetate, octadecyltrimethylammonium chloride, beef tallow trimethylammonium chloride, dodecyltrimethylammonium chloride, coconut trimethylammonium chloride, hexadecyltrimethylammonium chloride, behenyltrimethylammonium chloride, coconut dimethylbenzyl ammonium chloride, and tetradecyldimethylbenzyl. Examples of suitable alkylamine salts include ammonium chloride, octadecyldimethylbenzylammonium chloride, dioleyldimethylammonium chloride, 1-hydroxyethyl-2-beef tallow imidazoline quaternary salt, 2-heptadecenyl-hydroxyethyl imidazoline, stearamidoethyl diethylamine acetate, stearamidoethyl diethylamine hydrochloride, triethanolamine monostearate formate, alkylpyridinium salts, higher alkylamine ethylene oxide adducts, polyacrylamide amine salts, modified polyacrylamide amine salts, and perfluoroalkyl quaternary ammonium iodides.

[0059] Examples of amphoteric surfactants include dimethyl coconut betaine, dimethyl lauryl betaine, sodium lauryl aminoethyl glycine, sodium lauryl aminopropionate, stearyl dimethyl betaine, lauryl dihydroxyethyl betaine, amido betaine, imidazolinium betaine, lecithin, 3-[ω-fluoroalkanoyl-N-ethylamino] -1-sodium propanesulfonate, N-[3-(perfluorooctanesulfonamido)propyl]-N,N-dimethyl-N-carboxymethylene ammonium betaine, etc.

[0060] Examples of nonionic surfactants include coconut fatty acid diethanolamide (1:2 type), coconut fatty acid diethanolamide (1:1 type), cow fatty acid diethanolamide (1:2 type), cow fatty acid diethanolamide (1:1 type), oleic acid diethanolamide (1:1 type), hydroxyethyl laurylamine, polyethylene glycol laurylamine, polyethylene glycol coconut amine, polyethylene glycol stearylamine, polyethylene glycol tallow amine, polyethylene glycol tallow propylene diamine, polyethylene glycol dioleylamine, dimethyl laurylamine oxide, dimethyl stearylamine oxide, dihydroxyethyl laurylamine oxide, perfluoroalkylamine oxide, polyvinylpyrrolidone, higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, fatty acid ethylene oxide adducts, polypropylene glycol ethylene oxide adducts, fatty acid esters of glycerin, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol, fatty acid esters of sorbitan, and fatty acid esters of sugar.

[0061] Among the above-mentioned surfactants, sulfonic acid type surfactants such as alkylbenzenesulfonic acid, oil-soluble alkylbenzenesulfonic acid, α-olefinsulfonic acid, sodium alkylbenzenesulfonate, oil-soluble alkylbenzenesulfonate, and α-olefinsulfonate are suitable as dispersants from the viewpoints of the carbon dispersing effect, changes in catalyst performance due to residual dispersant, and the like.

[0062] Increasing the amount of polyelectrolyte in the catalyst ink generally reduces the pore volume, while increasing the amount of carbon particles in the catalyst ink increases the pore volume, and the use of a dispersant also reduces the pore volume.

[0063] In addition, the catalyst ink may be subjected to a dispersion treatment as necessary. The viscosity of the catalyst ink and the size of the particles contained in the catalyst ink can be controlled by the conditions of the dispersion treatment of the catalyst ink. The dispersion treatment can be performed by employing various devices. In particular, the method of the dispersion treatment is not limited. For example, the dispersion treatment may be a treatment using a ball mill and a roll mill, a treatment using a shear mill, a treatment using a wet mill, an ultrasonic dispersion treatment, or the like. In addition, a homogenizer that stirs by centrifugal force may be employed for the dispersion treatment. As the dispersion time for which the catalyst ink is subjected to the dispersion treatment increases, the aggregates of the catalyst-supported particles are destroyed, and therefore the pore volume becomes smaller in the electrode catalyst layer formed using the catalyst ink.

[0064] If the solid content in the catalyst ink is too high, the viscosity of the catalyst ink increases, and cracks are likely to occur on the surfaces of the electrode catalyst layers 2 and 3. On the other hand, if the solid content in the catalyst ink is too low, the film formation rate is very slow, and productivity decreases. Therefore, the solid content in the catalyst ink is preferably 1% by mass (wt%) or more and 50% by mass or less. That is, by having the solid content in the catalyst ink be 1% by mass or more, it is possible to prevent the film formation rate from becoming excessively low, and thus to prevent a decrease in productivity. By having the solid content in the catalyst ink be 50% by mass or less, it is possible to prevent the viscosity of the catalyst ink from becoming excessively high, and thus to prevent cracks from occurring on the surfaces of the electrode catalyst layers 2 and 3.

[0065] The solid content in the catalyst ink is composed of catalyst-supported particles, oxide-based catalyst material, fibrous material, and polymer electrolyte. When the content of the catalyst-supported particles, oxide-based catalyst material, and fibrous material in the solid content is increased, the viscosity becomes higher than when the content of the polymer electrolyte is greater, even if the solid content is the same. On the other hand, when the content of the catalyst-supported particles, oxide-based catalyst material, and fibrous material in the solid content is decreased, the viscosity becomes lower than when the content of the polymer electrolyte is greater, even if the solid content is the same. Therefore, the ratio of the catalyst-supported particles, oxide-based catalyst material, and fibrous material to the solid content is preferably within the range of 10% by mass to 80% by mass. In addition, the viscosity of the catalyst ink is preferably about 0.1 cP to 500 cP (0.0001 Pa·s to 0.5 Pa·s), and more preferably 5 cP to 100 cP (0.005 Pa·s to 0.1 Pa·s). Furthermore, the viscosity of the catalyst ink can be controlled by adding a dispersant when dispersing the catalyst ink.

[0066] The catalyst ink may also contain a pore-forming agent. The pore-forming agent can be used to form pores in the electrode catalyst layer by removing the pore-forming agent after the electrode catalyst layer is formed. Examples of the pore-forming agent include substances that dissolve in acids, alkalis, and water, substances that sublimate such as camphor, and substances that decompose thermally. For example, if the pore-forming agent is a substance that dissolves in hot water, the pore-forming agent may be removed from the electrode catalyst layer by water that is generated during power generation of a polymer electrolyte fuel cell equipped with the electrode catalyst layer.

[0067] Examples of pore-forming agents that are soluble in acid, alkali, or water include acid-soluble inorganic salts, inorganic salts soluble in an aqueous alkali solution, metals soluble in acid or alkali, water-soluble inorganic salts, water-soluble organic compounds, etc. Examples of acid-soluble inorganic salts include calcium carbonate, barium carbonate, Examples of inorganic salts soluble in alkaline aqueous solutions include magnesium carbonate, magnesium sulfate, and magnesium oxide. Examples of inorganic salts soluble in alkaline aqueous solutions include alumina, silica gel, and silica sol. Examples of metals soluble in acid or alkali include aluminum, zinc, tin, nickel, and iron. Examples of water-soluble inorganic salts include sodium chloride, potassium chloride, ammonium chloride, sodium carbonate, sodium sulfate, and monosodium phosphate. Examples of water-soluble organic compounds include polyvinyl alcohol and polyethylene glycol.

[0068] The above-mentioned pore-forming agents may be used alone or in combination of two or more kinds, but it is preferable to use two or more kinds in combination.

[0069] Examples of the method that can be used to apply the catalyst ink onto the substrate include a doctor blade method, a dipping method, a screen printing method, and a roll coating method.

[0070] The substrate used in the manufacture of the electrode catalyst layers 2 and 3 may be a transfer sheet. The transfer sheet used as the substrate may be formed of a material having good transferability. A fluororesin may be used as a material for forming the transfer sheet. The fluororesin may be, for example, ethylene tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroperfluoroalkylvinylether copolymer (PFA), polytetrafluoroethylene (PTFE), or the like. The substrate may be a polymer sheet or a polymer film. The material for forming the polymer sheet or the polymer film may be, for example, polyimide, polyethylene terephthalate, polyamide (nylon (registered trademark)), polysulfone, polyethersulfone, polyphenylene sulfide, polyether ether ketone, polyetherimide, polyarylate, polyethylene naphthalate, or the like. Furthermore, when a transfer sheet is used as the base material, an electrode catalyst layer, which is a coating film from which the solvent has been removed, is bonded to both sides of the polymer electrolyte membrane 1, and then the transfer sheet is peeled off from the electrode catalyst layer, thereby forming a membrane electrode assembly 11 having the electrode catalyst layers 2, 3 on both sides of the polymer electrolyte membrane 1.

[0071] A material having gas diffusibility and electrical conductivity can be used as a material for forming the gas diffusion layers 4 and 5. For example, a porous carbon material can be used as the gas diffusion layers 4 and 5. The porous carbon material may be, for example, carbon cloth, carbon paper, nonwoven fabric, etc.

[0072] The separators 10a and 10b may be carbon or metal type separators. The gas diffusion layers 4 and 5 and the separators 10a and 10b may each be integrally formed. That is, the gas diffusion layer 4 and the separator 10a may be integrally formed, and the gas diffusion layer 5 and the separator 10b may be integrally formed. In addition, when the separators 10a and 10b or the electrode catalyst layers 2 and 3 function as the gas diffusion layers 4 and 5, the gas diffusion layers 4 and 5 may be omitted. The solid polymer electrolyte fuel cell 12 is manufactured by assembling associated devices such as a gas supply device and a cooling device (not shown).

[0073] <Other effects> As described above, this embodiment describes a membrane electrode assembly 11 that exhibits high power generation characteristics under highly humidified conditions, a manufacturing method for the membrane electrode assembly 11, and a polymer electrolyte fuel cell 12 including the membrane electrode assembly 11. In the electrode catalyst layers 2 and 3 of the membrane electrode assembly 11 of this embodiment, entanglement of fibrous materials suppresses the occurrence of cracks in the electrode catalyst layers that cause a decrease in durability, thereby obtaining high durability and mechanical characteristics.

[0074] In addition, pores are formed in the electrode catalyst layer due to the entanglement of the catalyst-supporting particles, the oxide-based catalyst material, and the fibrous material. The pores in the electrode catalyst layer enable the discharge of water produced in the electrode reaction in the high current region during operation of the polymer electrolyte fuel cell, and increase the diffusibility of the reaction gas. The membrane electrode assembly manufactured by the manufacturing method of the electrode catalyst layer according to this embodiment has improved drainage properties in a high current region where a large amount of water is generated, without inhibiting water retention under low humidification conditions, and also exhibits high power generation performance and durability even under high humidification conditions. Furthermore, the manufacturing method of the electrode catalyst layer according to this embodiment can efficiently and economically easily, i.e., inexpensively manufacture the above-mentioned membrane electrode assembly.

[0075] That is, the above-mentioned membrane electrode assembly can be manufactured by forming an electrode catalyst layer using a catalyst ink in which a platinum-supported carbon catalyst (catalyst-supported particles), i.e., carbon particles supporting a platinum catalyst, an oxide-based catalyst material, a fibrous material, and a polymer electrolyte are dispersed in a solvent.

[0076] Therefore, the electrode can be manufactured without any complicated manufacturing process, and the use of the electrode catalyst layer manufactured by the above-mentioned procedure improves both water retention and the diffusibility of the reaction gas. Therefore, the electrode catalyst layer can be manufactured without providing a special means such as a humidifier, and as a result, costs can be reduced.

[0077] Only one of the electrode catalyst layers 2, 3 formed on both sides of the polymer electrolyte membrane 1 may be the first electrode catalyst layer. In that case, as described above, the first electrode catalyst layer is preferably an electrode catalyst layer that forms the air electrode (cathode) where water is generated by an electrode reaction, that is, the positive electrode.

[0078] Although the embodiments of the present disclosure have been described in detail above, in reality, the present disclosure is not limited to the above-described embodiments, and even if there are modifications within the scope of the present disclosure that do not deviate from the gist of the present disclosure, they are included in the present disclosure. EXAMPLES

[0079] The method for producing the first electrode catalyst layer and the membrane electrode assembly for a polymer electrolyte fuel cell according to the present embodiment will be described below with reference to specific examples and comparative examples. However, the present embodiment is not limited to the following examples and comparative examples.

[0080] In the following examples and comparative examples, the pair of electrode catalyst layers are both first electrode catalyst layers, but as described above, only one of the pair of electrode catalyst layers may be the first electrode catalyst layer.

[0081] <Example 1> [Preparation of catalyst ink] A platinum-supported carbon catalyst (catalyst-supported particles) with a support density of 50% by mass, an oxide-based catalyst material (TiONP), carbon fibers with an average fiber diameter of 150 nm and an average fiber length of 6 μm, and a 25% by mass polymer electrolyte solution were mixed in a solvent, and a dispersion process was performed in the solvent using a planetary ball mill. At this time, the dispersion time was set to 30 minutes, and a catalyst ink was prepared. The composition ratio of the starting materials in the prepared catalyst ink was set as follows. That is, the mass ratio of carbon support: oxide-based catalyst material: carbon fibers: polymer electrolyte was set to 1:1.4:0.2:0.8. A solvent in which ultrapure water and 1-propanol were mixed was used as the solvent for the catalyst ink. In the solvent, the volume ratio of ultrapure water to 1-propanol was set to 1:1. In addition, the catalyst ink was prepared so that the solid content in the catalyst ink was 12% by mass.

[0082] [Base material] A polytetrafluoroethylene (PTFE) sheet was used as the base material constituting the transfer sheet.

[0083] [Method of forming an electrode catalyst layer on a substrate] The catalyst ink prepared above was applied onto a substrate by a doctor blade method and dried in an air atmosphere at 80° C. The amount of catalyst ink applied was adjusted so that the platinum loading amount in the electrode catalyst layer forming the fuel electrode (anode) was 0.05 mg / cm. 2 In addition, the amount of platinum supported in the electrode catalyst layer forming the air electrode (cathode) is 0.1 mg / cm 2 The values ​​were adjusted so that

[0084] [Preparation of Membrane Electrode Assembly] The substrate on which the anode electrode catalyst layer was formed and the substrate on which the cathode electrode catalyst layer was formed were each punched out into a 5 cm x 5 cm square shape and transferred onto both sides of a polymer electrolyte membrane. That is, for a pair of opposing surfaces of the polymer electrolyte membrane, the anode electrode catalyst layer was transferred onto the first surface, and the cathode electrode catalyst layer was transferred onto the second surface. At this time, the transfer temperature was set to 130°C, and the transfer pressure was set to 5.0 x 10 6The pressure was set to 50 Pa. In this way, the membrane electrode assembly of Example 1 was produced.

[0085] <Comparative Example 1> [Preparation of catalyst ink] A platinum-supported carbon catalyst (catalyst-supported particles) with a support density of 50% by mass, carbon fibers with an average fiber diameter of 150 nm and an average fiber length of 6 μm, and a 25% by mass polymer electrolyte solution were mixed in a solvent, and a dispersion process was performed in the solvent using a planetary ball mill. At this time, the dispersion time was set to 30 minutes, and a catalyst ink was prepared. The composition ratio of the starting materials in the prepared catalyst ink was set as follows. That is, the mass ratio of carbon support:carbon fiber:polymer electrolyte was set to 1:0.2:0.8. A solvent in which ultrapure water and 1-propanol were mixed was used as the solvent for the catalyst ink. The volume ratio in the solvent was set to 1:1. The catalyst ink was also prepared so that the solid content in the catalyst ink was 12% by mass.

[0086] [Base material] A polytetrafluoroethylene (PTFE) sheet was used as the base material constituting the transfer sheet.

[0087] [Method of forming an electrode catalyst layer on a substrate] The catalyst ink prepared above was applied onto a substrate by a doctor blade method and dried in an air atmosphere at 80° C. The amount of catalyst ink applied was adjusted so that the platinum loading amount in the electrode catalyst layer forming the fuel electrode (anode) was 0.05 mg / cm. 2 In addition, the amount of platinum supported in the electrode catalyst layer forming the air electrode (cathode) is 0.1 mg / cm 2 The values ​​were adjusted so that

[0088] [Preparation of Membrane Electrode Assembly] The substrate on which the anode electrode catalyst layer was formed and the substrate on which the cathode electrode catalyst layer was formed were each punched out into a 5 cm x 5 cm square shape and transferred onto both sides of a polymer electrolyte membrane. That is, for a pair of opposing surfaces of the polymer electrolyte membrane, the anode electrode catalyst layer was transferred onto the first surface, and the cathode electrode catalyst layer was transferred onto the second surface. At this time, the transfer temperature was set to 130°C, and the transfer pressure was set to 5.0 x 10 6 The pressure was set to 50 Pa. In this way, a membrane electrode assembly of Comparative Example 1 was produced.

[0089] <Comparative Example 2> [Preparation of catalyst ink] A platinum-supported carbon catalyst (catalyst-supported particles) with a support density of 50% by mass, an oxide-based catalyst material (TiONP), and a 25% by mass polymer electrolyte solution were mixed in a solvent, and a dispersion process was performed in the solvent using a planetary ball mill. At this time, the dispersion time was set to 30 minutes, and a catalyst ink was prepared. The composition ratio of the starting materials in the prepared catalyst ink was set as follows. That is, the mass ratio of carbon support: oxide-based catalyst material: polymer electrolyte was set to 1:1.4:0.8. A solvent in which ultrapure water and 1-propanol were mixed was used as the solvent for the catalyst ink. In the solvent, the volume ratio of ultrapure water to 1-propanol was set to 1:1. The catalyst ink was also prepared so that the solid content in the catalyst ink was 12% by mass.

[0090] [Base material] A polytetrafluoroethylene (PTFE) sheet was used as the base material constituting the transfer sheet.

[0091] [Method of forming an electrode catalyst layer on a substrate] The catalyst ink prepared above was applied onto a substrate by a doctor blade method and dried in an air atmosphere at 80° C. The amount of catalyst ink applied was adjusted so that the platinum loading amount in the electrode catalyst layer forming the fuel electrode (anode) was 0.05 mg / cm. 2 In addition, the amount of platinum supported in the electrode catalyst layer forming the air electrode (cathode) is 0.1 mg / cm 2 The values ​​were adjusted so that

[0092] [Preparation of Membrane Electrode Assembly] The substrate on which the anode electrode catalyst layer was formed and the substrate on which the cathode electrode catalyst layer was formed were each punched out into a 5 cm x 5 cm square shape and transferred onto both sides of a polymer electrolyte membrane. That is, for a pair of opposing surfaces of the polymer electrolyte membrane, the anode electrode catalyst layer was transferred onto the first surface, and the cathode electrode catalyst layer was transferred onto the second surface. At this time, the transfer temperature was set to 130°C, and the transfer pressure was set to 5.0 x 10 6 The pressure was set to 50 Pa. In this way, a membrane electrode assembly of Comparative Example 2 was produced.

[0093] <Evaluation> [Power generation characteristics] Carbon paper, which is a gas diffusion layer, was attached so as to sandwich each of the membrane electrode assemblies of Example 1 and Comparative Examples 1 and 2 to prepare samples. Each sample was then placed in a power generation evaluation cell, and current and voltage measurements were performed using a fuel cell measurement device. The cell temperature during measurement was set to 65°C, and the operating conditions were set to high humidification and low humidification as shown below. Hydrogen was used as the fuel gas, and air was used as the oxidizing gas. At this time, the flow rate of hydrogen was set to a flow rate at which the hydrogen utilization rate was 90%, and the flow rate of air was set to a flow rate at which the oxygen utilization rate was 40%. The back pressure was set to 50 kPa.

[0094] [Operating conditions] Condition 1 (high humidity): Relative humidity Anode: 90% RH, Cathode: 80% RH Condition 2 (low humidity): Relative humidity Anode: 90% RH, Cathode: 30% RH

[0095] [Measurement results] The polymer electrolyte fuel cell including the membrane electrode assembly of Example 1 exhibited superior power generation performance under highly humidified operating conditions than the polymer electrolyte fuel cells including the membrane electrode assemblies of Comparative Examples 1 and 2. It was also confirmed that the membrane electrode assembly of Example 1 had the same power generation performance under highly humidified operating conditions as under low humidified operating conditions. In particular, the membrane electrode assembly of Example 1 was found to have a current density of 1.5 A / cm 2Power generation in the vicinity has improved.

[0096] Under highly humidified operating conditions, the solid polymer electrolyte fuel cell equipped with the membrane electrode assembly of Example 1 had a current density of 1.5 A / cm 2 The cell voltage in the solid polymer electrolyte fuel cell having the membrane electrode assembly of Comparative Example 1 was 1.5 A / cm 2 It was found that the cell voltage at a current density of 1.5 A / cm was 0.26 V higher than that at a current density of 1.5 A / cm in the solid polymer electrolyte fuel cell equipped with the membrane electrode assembly of Example 1 under highly humidified operating conditions. 2 The cell voltage in the solid polymer electrolyte fuel cell having the membrane electrode assembly of Comparative Example 2 was 1.5 A / cm 2 It was found that the cell voltage at the current density was 0.22 V higher than that at the current density of 100 V.

[0097] From the measurement results of the power generation performance of a polymer electrolyte fuel cell including the membrane electrode assembly of Example 1 and the power generation characteristics of polymer electrolyte fuel cells including the membrane electrode assemblies of Comparative Examples 1 and 2, it was confirmed that the membrane electrode assembly of Example 1 improves drainage properties, and therefore the power generation characteristics under high humidification operating conditions are equivalent to those under low humidification operating conditions.

[0098] Moreover, under low humidification operating conditions, the polymer electrolyte fuel cell equipped with the membrane electrode assembly of Example 1 had a current of 1.5 A / cm 2 The cell voltage at a current density of 1.5 A / cm in the solid polymer electrolyte fuel cell equipped with the membrane electrode assembly of Comparative Example 1 2 It was also found that the cell voltage at a current density of 1.5 A / cm was 0.28 V higher than that at a current density of 1.5 A / cm in the solid polymer electrolyte fuel cell equipped with the membrane electrode assembly of Example 1 under low humidification operating conditions. 2 The cell voltage at a current density of 1.5 A / cm in the solid polymer electrolyte fuel cell equipped with the membrane electrode assembly of Comparative Example 2 2 It was found that the cell voltage at the current density was 0.24 V higher than that at the current density of 100 V.

[0099] From the measurement results of the power generation performance of a polymer electrolyte fuel cell including the membrane electrode assembly of Example 1 and the power generation characteristics of polymer electrolyte fuel cells including the membrane electrode assemblies of Comparative Examples 1 and 2, it was confirmed that the membrane electrode assembly of Example 1 has high drainage properties of water generated in the electrode reaction and does not inhibit water retention under low humidification conditions. [Explanation of symbols]

[0100] 1...Polymer electrolyte membrane 2...Electrode catalyst layer 3...Electrode catalyst layer 4...Gas diffusion layer 5...Gas diffusion layer 6...Air electrode (cathode) 7...Fuel electrode (anode) 8a, 8b...Gas flow path 9a, 9b...Cooling water flow path 10a, 10b...Separator 11...Membrane electrode assembly 12...Polymer fuel cell

Claims

1. A polymer electrolyte membrane and a pair of electrode catalyst layers sandwiching the polymer electrolyte membrane, At least one of the pair of electrode catalyst layers includes particles carrying a catalyst made of a precious metal component, a polymer electrolyte, a fibrous material having an average fiber length falling within a range of 1 μm or more and 15 μm or less, and an oxide-based catalyst material, The oxide-based catalytic material contains a transition metal element, The transition metal element is Ti. Membrane electrode assembly for fuel cells.

2. The electrode catalyst layer containing the particles, the polymer electrolyte, the fibrous material, and the oxide-based catalyst material includes an electrode catalyst layer for a positive electrode in a polymer electrolyte fuel cell. The membrane electrode assembly for a fuel cell according to claim 1 .

3. The oxide-based catalytic material is a material in which the nitride of the transition metal element contains P as a substitution atom and the nitride is partially oxidized.

3. The membrane electrode assembly for a fuel cell according to claim 1 or 2.

4. The ratio (MB / MA) of the mass (MB) of the oxide-based catalyst material to the mass (MA) of the carrier in the particles carrying the catalyst made of the precious metal component is within the range of 0.1 to 10 times. The membrane electrode assembly for a fuel cell according to claim 1 .

5. The ratio (MC / MA) of the mass (MC) of the polymer electrolyte to the mass (MA) of the carrier in the particles carrying the catalyst made of the precious metal component is within the range of 0.2 to 2.8 times. The membrane electrode assembly for a fuel cell according to claim 1 .

6. The ratio (MD / MA) of the mass (MD) of the fibrous material to the mass (MA) of the carrier in the particles carrying the catalyst made of the precious metal component is within the range of 0.05 times or more and 1.0 times or less. The membrane electrode assembly for a fuel cell according to claim 1 .

7. The particles carrying the catalyst made of the precious metal component are covered with a hydrophobic coating. The membrane electrode assembly for a fuel cell according to claim 1 .

8. The fuel cell membrane electrode assembly according to any one of claims 1 to 7, a pair of gas diffusion layers sandwiching the fuel cell membrane electrode assembly; a pair of separators sandwiching the pair of gas diffusion layers; Polymer electrolyte fuel cell.

Citation Information

Patent Citations

  • Electrocatalyst, its manufacturing method, and fuel cell using electrocatalyst

    JP2005044659A

  • Fuel cell

    JP2005063677A

  • Electrode for polymer electrolyte fuel cell and manufacturing method of membrane / electrode assembly utilizing the same

    JP2011119217A

  • Fuel cell electrode and method for manufacturing membrane electrode assembly using the same

    JP2013084540A

  • Electrode material for water electrolysis and method for producing the same, and electrode for water electrolysis

    JP2017179408A